Optimizing Patient Management and Adherence for Children Receiving Growth Hormone - Acerini, Carlo L.; Wac, Katarzyna; Bang, Peter; Lehwalder, Dagmar (Frontiers in Endocrinology, 2017)
The abstract has been revised to reflect the amendments suggested by the peer reviewers to the core manuscript. Unfortunately this has now taken the abstract word count over the required limit within the submission site. Please refer to the abstract within the manuscript document.